Kina na Dolnym Śląsku: rekonesans historyczny - Andrzej Dębski, Andrzej Dębski (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The highest level of cinema attendance in Lower Silesia after World War II was recorded in 1957. It was higher than before the war and lower than during the war. In the years that followed it steadily declined, influenced by global processes, especially the popularity of television. This leads us to reflect on the continuity of historical and film processes, and to look at the period from the 1920s to the 1960s as the ‘classical’ period in the history of cinema, when it was the main branch of mass entertainment. The examples of three Lower Silesian cities of different size classes (Wroclaw, Jelenia Gora, Strzelin) show how before World War II the development from ‘the store cinema [or the kintopp] to the cinema palace’ proceeded. Attention is also drawn to the issue of the destruction of cinematic infrastructure and its post-war reconstruction. In 1958 the press commented that ‘if someone produced a map with the towns marked in which cinemas were located, the number would increase as one moved westwards’. This was due to Polish (post-war) and German (pre-war) cinema building. The discussion closes with a description of the Internet Historical Database of Cinemas in Lower Silesia, which collects data on cinemas that once operated or are now operating in the region.